Konsepsi Kebahagiaan dalam Perspektif Filsafat dan Tasawuf - Jonsi Hunadar (IAIN Bengkulu, 2022)
Happiness in real life is sometimes manifested in the perception of each individual in interpreting it. The form and method of obtaining it may differ from one individual to another. The study in this paper the author will discuss about happiness in the perspective of philosophy and Sufism. The method used in this paper is literature study in which the main source comes from literature consisting of books and scientific journal articles. The results of the research show that in the study of philosophy the highest goodness of humans is called happiness, and to achieve this a human being is required to do goodness and virtue. According to Sufis, the worldly sometimes often makes people forget, whereas actually being happy is always being close to Allah swt.